Visualizzazione stereoscopica collaborativa di geodati tridimensionali con software libero - Frigeri, Alessandro; Federico, Costanzo (GEOmedia, 2012)
La visualizzazione dell'informazione sussiste da quando esiste l'informazione stessa e nasce dalla necessità sia dicomprendere meglio particolari aspetti di un insieme di dati, sia di comunicarli. Collaborative three-dimensional stereoscopic visualization of geodata with free software Geodata are inherently three-dimensional, when referred to heights and depths. This article describes the development and applications of a interactive and collaborative stereoscopic visualization system built by off-the-shelf hardware and focusing on the use of a completely free open source software stack, from the operative system to the graphics drivers and the users space applications.